138 DELAYED BLOOD PRESSURE RECOVERY AFTER STANDING INDEPENDENTLY PREDICTS FRACTURE IN COMMUNITY-DWELLING OLDER PEOPLE. (18th November 2021) - Doyle, K; Lavan, A; Kenny, R-A; Briggs, R
Abstract: Background: Orthostatic hypotension, characterized by delayed blood pressure recovery (DBPR) after standing, is a risk factor for falls but the longitudinal relationship with fracture is not yet known. The aim of this study was to examine the prospective risk of fracture associated with DBPR. Methods: This study, embedded within the Irish Longitudinal Study on Ageing (TILDA), examined prospective risk of fracture (hip, wrist or vertebral) associated with DBPR at 8-year follow-up in a population-representative sample of more than 3, 000 (54% female) community-dwelling older people. Orthostatic blood pressure (BP) was measured using a finometer during active stand at TILDA Wave 1. DBPR was defined as systolic BP ≤ 20 mmHg lower and/or diastolic BP ≤ 10 mmHg from baseline value at 30, 60 and 90 seconds after standing. Participants with a fracture reported at any of Waves 2–5 were defined as having 'Incident Fracture'. Logistic regression models were used to estimate odds ratios (ORs) for the association between DBPR and incident fracture. Results: Seven percent (212/3117) of participants sustained a fracture during follow-up. DBPR at 30 seconds was a significant predictor of any fracture [OR 1.80, 95% confidence interval (CI) 1.28–2.53] and hip fracture (OR 4.44, 95% CI 2.03–9.71) in fully adjusted models. DBPR at 30 seconds did not predict wrist or vertebral fracture. DBPR at 60 seconds also predicted any fracture (OR 1.74, 95% CI 1.19–2.54) and hip fracture (OR 4.66, 95% CI 2.12–10.26) whereas DBPR at 90 seconds predicted any (OR 1.99, 95% CI 1.38–2.87), wrist (OR 1.87, 95% CI 1.19–2.95), and hip fracture (OR 3.39, 95% CI 1.45–7.93) in fully adjusted models. Conclusion: Delayed BP recovery independently predicts fracture in community-dwelling older people, is potentially modifiable, and can be measured in an ambulatory setting. Given the morbidity and mortality associated with fractures, identification of such risk factors is crucial in order to inform preventative strategies.